THE URGENCY AND STRATEGY OF IC-CEPA INTERNATIONAL COOPERATION ON THE ECONOMIC DEVELOPMENT OF INDONESIA - Rosita, Ita; Rachmah, Octazia Zauzah; Jaelani, Achmad; Mohas, Muhyi; Tajudin, Amalina Ahmad (Tirtayasa Journal of International Law, 2024)
International cooperation is one of the solutions to several economic problems of a country. Indonesia-Chile's internationalcooperation has yielded many results, one of which is a surplus of 85% in 2020. From the many positive things that have an impact on this cooperation, it is an urgency to be able to develop the Indonesian economy in various sectors, not only in the manufacturing, services and agriculture sectors but also more spread for a more comprehensive Indonesian economy and trade. Internationalcooperation between Indonesia and Chile must also be based on a sustainable economy, which means that the strategy that must be built includes not only social and economic aspects but also the environment. The research method used is a normative method where research is based on credible books and journals. Based on the data of Chile's total imports from Indonesia (in thousands of USD) 183,458 with a growth of -7% from 2011 to 2015 and only 0.3% of Chile's total imports. So with the existence of severalregulations, finally the international cooperation of Indonesia Chile Comprehensive Economic Partnership Agreement (CEPA) will realize international cooperation agreements in many sectors with many other countries